Review of Sharia Perspective of Online Forex and Gold Trading Through MetaTrader 4 and MetaTrader 5 Platforms at Futures Brokers in Indonesia - Prasetya, Ilham; Fadila, Nisa Rahma (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2025)
Background: The COVID-19 pandemic significantly impacted society’s economy. Various industry sectors stopped operating, which resulted in widespread layoffs. As a result, society tends to make online financial transactions, particularly with forex and gold. Objectives: This study examines Islamic law's perspective on online forex and gold futures trading, which is increasingly popular among the public. Novelty: Academic literature specifically conducting a juridical deconstruction (takyif fiqh) of the 'rolling contracts' offered in Indonesia and identifying them as Contracts for Difference (CFDs) remains scarce. A 2021 study noted that